Cyber Security in International Conflict: US China Cyber Competition and Its Impact on India (Journal of Social Sciences Review, 2025)
The rising cyber rivalry between China and the United States is the significant part of modern-day global conflict, with far-reaching consequences for global security, economic stability, and geopolitical power balance. The nature of cyber competition between US-China cyber is examined in this paper, with a focus on cyber espionage, digital warfare, and artificial intelligence-powered cyber capabilities. It examines how this rivalry impacts India's national security, technological advancement and diplomatic status in the Indo-Pacific area are affected by this rivalry. Using theories of international relations like as realism and the security dilemma, the paper examines the strategic objectives behind cyber operations and their cascading implications on third-party nations such as India. The findings suggest that, while cyber rivalry exacerbates regional instability, it also forces India to strengthen its cyber defenses and form develop strategic alliances, so thereby shaping its role as a crucial actor in the changing digital geopolitical environment.
Keywords: US-China Cyber Rivalry; Cyber Warfare; Technological Sovereignty; Cyber Espionage